2016
DOI: 10.1175/jtech-d-16-0100.1
|View full text |Cite
|
Sign up to set email alerts
|

Intercalibration of the GPM Microwave Radiometer Constellation

Abstract: The Global Precipitation Measurement (GPM) mission is a constellation-based satellite mission designed to unify and advance precipitation measurements using both research and operational microwave sensors. This requires consistency in the input brightness temperatures (Tb), which is accomplished by intercalibrating the constellation radiometers using the GPM Microwave Imager (GMI) as the calibration reference. The first step in intercalibrating the sensors involves prescreening the sensor Tb to identify and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
71
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(82 citation statements)
references
References 53 publications
1
71
0
Order By: Relevance
“…Multiple independent approaches are compared during these steps, which help to identify flaws or limitations of a given approach, thus increasing confidence in the results and providing a measure of the uncertainty in the resulting calibration adjustments. After adjustments, residual differences between GMI channels and those on the constellation radiometers are generally smaller than 1 K (Berg et al 2016). This is a remarkable achievement that now allows the project to focus on the precipitation products rather than T B uncertainties.…”
Section: Algorithms Data Pro D U Ct S Data Processing and Data Avmentioning
confidence: 98%
See 1 more Smart Citation
“…Multiple independent approaches are compared during these steps, which help to identify flaws or limitations of a given approach, thus increasing confidence in the results and providing a measure of the uncertainty in the resulting calibration adjustments. After adjustments, residual differences between GMI channels and those on the constellation radiometers are generally smaller than 1 K (Berg et al 2016). This is a remarkable achievement that now allows the project to focus on the precipitation products rather than T B uncertainties.…”
Section: Algorithms Data Pro D U Ct S Data Processing and Data Avmentioning
confidence: 98%
“…Sensor intercalibration between GMI and the partner sensors involves several steps, as described in Wilheit (2013), Wilheit et al (2015), and Berg et al (2016). Multiple independent approaches are compared during these steps, which help to identify flaws or limitations of a given approach, thus increasing confidence in the results and providing a measure of the uncertainty in the resulting calibration adjustments.…”
Section: Algorithms Data Pro D U Ct S Data Processing and Data Avmentioning
confidence: 99%
“…Subsequently, Wentz and Draper (2016) concluded that GMI is the most accurate precipitation radiometer currently in space. To provide unified global precipitation estimates a reliable transfer standard of brightness temperatures (Tbs) between the GPM-CO and the constellation partner precipitation sensors through the inter-calibration of all the radiometer sensors has been established (Berg et al, 2016). This inter-calibration effort ensures that the observed Tbs are consistent among the sensors allowing for expected differences due to variations in the observing frequencies, bandwidths, polarizations, and view angles (e.g.…”
Section: Progress Toward Advancing Precipitation Measurementsmentioning
confidence: 99%
“…Wilheit et al, 2015). After inter-calibration, residual differences between the GMI Tbs and those of the constellation radiometers are generally smaller than 1 K (Berg et al, 2016). These GPM inter-calibrated Tbs are made available on the NASA PPS and are the first step toward unified precipitation products.…”
Section: Progress Toward Advancing Precipitation Measurementsmentioning
confidence: 99%
“…As an ESDR, the CETB product leverages as input a new, (swath format) FCDR, which includes a completely reprocessed historical SSM/I and SSMIS record including new efforts to improve intersensor calibrations [29][30][31]. To ensure transparency and reproducibility, we populated provenance metadata in file-level attributes in each CETB file at runtime, to record the specific FCDR files used to derive the CETB image; software version tags for the gsx and core systems were automatically captured as file-level attributes.…”
Section: Climate and Forecast (Cf) Conventionsmentioning
confidence: 99%